Pemanfaatan Media Sosial "Facebook" Untuk Media Pembelajaran Bahasa Indonesia - Mayasari Sasmito (Media Aplikom, 2015)
Indonesian learning innovations are needed so that learning is not boring. One of them using facebook. Facebook is one of the social media that has features that applications use to communicate with other users, ranging from education, business, and entertainment. Many life activities developed in these social networking sites. With facebook teachers can play an active role by making group that is subjects related to Indonesian. With facebook teacher can also socialize with students on a variety of subject matter Indonesian. In addition, the teacher facebook to share material, either in the form of links, images and videos. This is to augment teaching materials. Consultation room, a summary of the material on the note, can be used as a media workout / evaluation by way of exercise or quiz students answer given by the teacher on facebook